Morphological and Molecular Study of Trogoderma granarium Everts, 1898in Iraq - Mzhr, Nassreen N.; Sabr, Ahmed J.; Jawad, Mohammed M. (Iraqi Journal of Science, 2025)
Trogoderma granarium Everts 1898, commonly known as the khapra beetle, is a widespread pest species affecting stored grains. Samples of this pest were collected from different geographical regions across four governorates in Iraq, namely Mosul, Salahdin, Dhi Qar, and two regions within Baghdad (Latifiya and Jamila). The current study provides a detailed description of T. granarium about the morphological characteristics of the three body regions and their appendages that studied and supported by illustrations. Due to the morphological similarity between this species and many closely related species, accurate identification is challenging, particularly when the stored materials are contaminated with insect remains. Therefore, molecular diagnosis was confirmed using PCR-based assays such as conventional PCR and DNA sequencing, targeting mitochondrial (mtDNA) genes like COI (Cytochrome Oxidase I) and 16S (16S rRNA). Results showed that there are many genetic variations in the nitrogenous bases of the samples under study compared with the standard samples results which was taken from global data, with differences between the local samples themselves, which indicates the multiple genetic sources from which the insects came as a result of the import of grains and perhaps their poor storage.